Pembantuan dalam Tindak Pidana Perjudian (Studi Putusan Nomor 94/Pid.B/2017/PN Gin) - I Nyoman Agus Suprapta; I Ketut Sukadana; I Made Minggu Widyantara (Jurnal Analogi Hukum, 2020)
Abstract—Gambling essentially is contrary to norms. In fact, gambling is increasingly done by people hide away or clearly. Other than gambling which has been well known and operated in some places in Indonesia, especially in bali like cock fighting, ceki(balinese card game), togel (black toto), bola adil and so on. Surely, it needs facilities and infrastructure to do that gambling. It makes willingness by an individual or a group of people to support to do gambling itself that giving chance to public for gambling. The problem in this research is how to regulate the assistance as one form of criminal act in Indonesia and how legal sanction done to the assistance in gambling criminal act that has been regulated on Number 94/Pid.B/2017/PN Gin. Research methods used in this research is normative research with the constitution and conceptual approach. After collecting all of legal materials, it will be processed and analyzed using legal argument, deductive inductive and formed descriptively into research. The result of this research can be concluded that the assistance as one of the form of criminal regulated in article 56 about the form of assistance, article 5 about assistance responsibility system and article 60 about assistance responsibility affirmation. The Judge, in giving legal sanction to the assistance suspect in gambling criminal act case number 94/Pid.B/2017/PN Gin. Has based on article 303 paragraph (1) point 2 KUHP in considering anything that relieving or burdening, case position, evidence of the witness and the suspect, and the Judge believes in giving a fair punishment.